Kocuria uropygioeca sp. nov. and Kocuria uropygialis sp. nov., isolated from the preen glands of Great Spotted Woodpeckers (Dendrocopos major) - Braun, Markus S.; Wang, Erjia; Zimmermann, Stefan; Boutin, Sébastien; Wink, Michael (Systematic and applied microbiology, 2018)
Two new species of Gram-positive cocci were isolated from the uropygial glands of wild woodpeckers (Dendrocopos major) originating from different locations in Germany. A polyphasic approach confirmed the affiliation of the isolates to the genus Kocuria. Phylogenetic analysis based on the 16S rRNA gene showed high degree of similarity to Kocuria koreensis DSM 23367T (99.0% for both isolates). However, low ANIb values of <80% unequivocally separated the new species from K. koreensis. This finding was further corroborated by DNA fingerprinting and analysis of polar lipid profiles. Furthermore, growth characteristics, biochemical tests, MALDI-TOF MS analysis, and G+C contents clearly differentiated the isolates from their known relatives. Besides, the woodpecker isolates significantly differed from each other in their whole-cell protein profiles, DNA fingerprints, and ANIb values. In conclusion, the isolated microorganisms constitute members of two new species, for which the names Kocuria uropygioeca sp. nov. and Kocuria uropygialis sp. nov. are proposed. The type strains are 36T (DSM 101740T=LMG 29265T) and 257T (=DSM 101741T=LMG 29266T) for K. uropygialis sp. nov. and K. uropygioeca sp. nov., respectively.
Gesehen am 14.02.2018